Upper Jurassic ammonites and bivalves from the Cucurpe Formation, Sonora (Mexico) - Ana Bertha Villaseñor; Carlos M. González-León; Timothy F. Lawton; Martin Aberhan (Revista Mexicana de Ciencias Geológicas)
Four new molluscan assemblages from north-central Sonora indicate that the Cucurpe Formation ranges in age from late Oxfordian to early Tithonian. These assemblages extend the known paleogeographic range of Late Jurassic Tethyan fossil groups several hundred km to the northwest and improve correlation of Upper Jurassic strata in northern Mexico. At Rancho La Colgada, near the town of Tuape, the upper part of the Cucurpe Formation consists of 515 m of shale, siltstone, basaltic ﬂows and minor sandstone. The oldest fossil assemblage is assigned to the Bifurcatus Zone of the lower upper Oxfordian and contains the ammonites Perisphinctes (Dichotomoceras?) sp., Sequeirosia? sp., and the bivalves Grammatodon (Grammatodon) hersilius (d´´´´´¨'´Orbigny), Parainoceramus sp., “Lucina” potosina Aguilera, “Lucina” sp., and Isocyprina? sp. The second assemblage is assigned to the lower Tithonian (lower part of the Albertinum/Darwini Zone) and consists of the ammonites Mazapilites mexicanus (Aguilera), Schaireria neoburgensis (Oppel), Subplanitoides sp., and Glochiceras (Lingulaticeras?) sp. The third fossil assemblage from the uppermost part of the section includes the ammonites Sublithacoceras cf. sphinctum (Schneid), Sublithacoceras sp., and Pachysphinctes sp., and the bivalves “Lucina” potosina Aguilera and Integricardium (Integricardium) sp. This assemblage belongs to the Semiforme-Verruciferum Zone to Richteri Zone of the middle lower Tithonian. A fourth assemblage is assigned to the lower Tithonian, representing the middle to upper part of the Albertinum-Darwini or the lowermost part of the Semiforme- Verruciferum Zone. This assemblage was collected from the upper part of the Cucurpe Formation at a nearby locality and contains the ammonites Torquatisphinctes subbleicheri (Burckhardt), T. cf. lauri (Aguilera) and Torquatisphinctes sp. cf. T. diversecostatus (Burckhardt). The absence of Kimmeridgian fossils in the measured section at Rancho La Colgada and a conglomerate between the Oxfordian and Tithonian assemblages combine to indicate an unconformity in the Upper Jurassic interval that omits the Kimmeridgian. A single Kimmeridgian ammonite was recently collected in the Cucurpe Formation about 40 km northwest of the study area.